(3GdeSFhdjI GdfGTFI Yf GdJUGOe GdHMQj (B: s (3OQGSI ebGQfI (B/ s - (3GdYGFT MSjf YGeQ GdhQadjs; (3CMeO aGQhb hTGMj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3YGdLJ gPg GdOQGSI GMO GdMhGOK GdHMQjI GdJi JYQVJ dgG GdSaf hGdGSS GdJi JMei gPg GdSaf hGdGehGd ef GdVjGY hQcRJ Ydi GcHQ MOK jecf Gf Jchf dg BKGQ LSjeI Ydi GdSajfI hGdGTNGU hGdHVGFY Ydi MO ShGA GdG hgh GdJUGOe GdHMQi hbSeJ GdOQGSI deHMK JegjOi NUU dOQGSI eGgjI GdJUGOe GdHMQi haUdjf QFjSSjf NUU GdGhd efgG dfWGb GdeSFhdjI GdfGTFI Yf GdJUGOe GdHMQi hGeG KGfjgeG dHjGf GdGKGQ GdbGfhfjI GdeJQJHI Ydi hbhY GdJUGOe hNdUJ GdOQGSI Gdi Gf ZGdHjI GdJTQjYGJ GdhWfjI JHfJ GMcGe eYGgOI HQhcSd dSfg (B1910(3GdNGUI HJhMjO HYV eSGFd GdJUGOe GdHMQi HGYJHGQgG fJGL JacjQ Ohdi Yejb hef Ke aGf GdMdhd GdJi GaVJ GdjgG GdeYGgOI gi GcKQ fJGLG ef Jdc GdJi jecf Gf jUd GdjgG GdeTQhY GdhWfis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2016(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B174-186s
Keywords: (3GdJbGQjQ GdHMQjIs; (3GdJUGOe GdHMQj s; (3GdSajfI s; (3GdQHGfs; (3GdQcGHs; (3GdHVGFYs; (3GdGQJWGes; (3OaJQ jhejI GdSajfIs; (3eYGgOI HQhcSds; (3eYGgOI dfOfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs